Availability of essential medicines, inventory management practices, and related challenges in internally displaced persons (IDP) camps, eastern Amhara, Ethiopia: an explanatory sequential mixed study - Tekletsadik Tekleslassie Alemayehu; Alem Endeshaw Woldeyohanins; Eskedar Dires Gebremeskel; Gebremariam Wulie Geremew; Yilkal Abebaw Wassie; Mekonnen Derese Mekete; Tefera Minwagaw; Tesfaye Birhanu Abebe; Kelemnesh Seifu (Conflict and Health)
Abstract Background The ongoing conflicts and natural disasters in Ethiopia have led to a significant increase in the number of Internally Displaced Persons (IDPs), necessitating effective healthcare delivery in IDP camps. This study aims to assess the availability of essential medicines and inventory management practices and to identify common challenges within these camps in Eastern Amhara, Ethiopia. Methods An explanatory sequential mixed method was employed, from August to October 2023, in 5 IDP camps in Eastern Amhara, Ethiopia. Structured and semi-structure questionnaires were utilized. Data were collected through face-to-face and telephone interview, document review, and observation. Quantitative data were entered into Epi Data version 4.6 and analyzed by SPSS window version 26, and descriptive statistics were computed and summarized results were presented by using text, tables and graphs, while thematic analysis using open code software was employed for qualitative data analysis. Results The average availability of essential medicines in IDP camps was 77.3%. Inventory control cards were available in nearly half of the OPDs clinics in IDP camps. However, the overall updating practice on transaction was 0%. None of the IDP camps met the criteria for acceptable storage conditions. Only 18.2% of OPD clinics are adhered to FEFO inventory control procedure. Common challenges affecting the availability of essential medicines and inventory management practices in IDP include poor inventory management practices, national stock outs, irrational drug use, fraud and theft, insecurity, inadequate infrastructure, uncertainty, reliance on push delivery systems, lack of inter-agency collaboration, and limited resources. Conclusion The study found that while the average availability of essential medicines in IDP camps was fairly- high, stockouts were common, and none of the camps met the established criteria for acceptable storage conditions. Inventory management practices were weak, with poor adherence to protocols such as bin card updating, stock level reviews, and the FEFO system. The current study suggest that significant efforts are being made to supply IDP camps with essential medicines, despite the challenges posed by poor inventory management, national-level stock shortages, irrational drug use, fraud and theft, insecurity, inadequate infrastructure, uncertainty, reliance on push delivery systems, lack of inter-agency collaboration, and limited resources.